STRATEGI MEMBANGUN BUDAYA BACA (Studi Kasus di Kelas 4 Ahmad Dahlan SDIT Salsabila 2 Klaseman Ngaglik Sleman) - Ahmad Safi’i (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
In Islam, the command to read occupies a major position, even the first revelation that the Prophet Muhammad received was an order to read. Indonesia is a country with the largest Muslim population in the world, ideally reading interest is high. But the facts say otherwise. Low interest in reading also occurred in Grade 4 Ahmad Dahlan SDIT Salsabila 2 Klaseman, even though the school library was already available with various books. The research method used is descriptive qualitative with field research. The research subjects were the 4th grade students of Ahmad Dahlan at SDIT Salsabila 2 Klaseman, teachers, principals and guardians of students. The results showed that the cause of children's low interest in reading was influenced by internal and external factors. Internal factors are in the form of student motivation, but these internal factors are influenced by external factors, namely education in the family environment, peers/play and the school environment. A good family or peer environment will lead children to have good habits, including reading. Meanwhile, external factors in the school environment include four things: (1) there is little rest time available, (2) the distance between the class and the library is quite far, (3) most peers fill their break time by playing, and (4) there is no model of habituation to the library from the teacher. Efforts made to improve a reading culture are: (1) utilizing the principal's policy on literacy, (2) making class libraries with beautiful designs, (3) cultivating a sense of belonging to class literature, making them together with materials and books from children , (4) supply of books from the class library, (5) provided playing equipment (sitting games) near the class library, (6) cooperate with student guardians, always discuss it at the monthly meeting, (7) provide rewards for those who diligently read, and (8) announcing the results of the reward in front of their friends, (9) the teacher sets an example of fondness for reading.